Exploring Women's Madrasahs in South Africa: Implications for the Construction of Muslim Personhood and Religious Literacy - Hoel, Nina (Religious education, 2016)
Set against the backdrop of a changing pluralistic South African society, this article traces the shifts concerning religion in public education, followed by an examination of the discernible motivations that undergirded the establishment of women's madrasahs (Islamic educational institutions). Collectively representing an alternative approach to education by acknowledging and preserving Muslim identity, history, and religiosity, madrasah education is also configured through particular understandings of gender and gender relations in Islam. Hence, in this article, I probe the extent to which women's madrasahs in South Africa introduce notions of gendered religious literacy and personhood, and whether these are fashioned along traditional gender scripts and ideals.